PENGARUH DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA CV SUMBER CIPTA AGUNG - Kho, Lucky; Hikmah, Hikmah (LPPM Universitas Putera Batam, 2022)
Human resources are one of the factors in an organization. . Every organization has the mastery of developing and improving the work of its employees. To improve what has been determined, the organization needs monitoring and at the same time improving itsemployees so that they can apply discipline at work. Work discipline is a step taken by the company to ensure that the company can be achieved. Although there is no guarantee that the company's goals will be achieved, all efforts must still be made. The company's goals can be obtained and disciplinary regulations can be implemented, thus it is necessary to provide a motivation or in other words provide work motivation to employees. Improved performance of employees can be profitable for the company, because with high work results, the productivity of work on employees will also increase. The research method in this study is a quantitative method with a population of 110 people. And sampling using non-probability sampling technique. The results of the study obtained that work discipline and work motivation had a positive and significant influence on the performance of CV Sumber Cipta Agung employees with a determination coefficient of 52.8%.